Adaptive multimedia delivery in WMSNs: Routing and resolution synergy - Abdulmoghni, Yosef A.; Alhomdy, Sharaf A.; Abdulrazaq, Fuaad H. (Edelweiss Applied Science and Technology, 2025)
The aim of the paper is to address the challenge of resource-efficient transmission in Wireless Multimedia Sensor Networks (WMSNs), with applications in environmental monitoring, healthcare, and surveillance. An adaptive framework is proposed, emphasizing routing adaptation and resolution adaptation based on principles of cross-layer design and intelligent fuzzy logic control. The approach utilizes a Mamdani-type fuzzy controller, which features four inputs residual energy, packet loss rate, end-to-end delay, relay power and two outputs routing adaptation level and resolution adaptation level governed by 180 fuzzy rules. Real images were employed in OMNET++ simulations, complemented by the XEMMU power simulator for precise energy consumption estimations. The proposed method demonstrates significant improvements over baseline protocols such as GPSR, EWHCP, and PDDQL, particularly in terms of packet delivery ratio, reduction in end-to-end delay, and energy efficiency, all while maintaining acceptable multimedia quality without compression. The study clearly illustrates that the intelligent, synergistic adaptation of routing and resolution without relying on compression is an effective strategy for QoS optimization with high resource efficiency in dynamic and constrained WMSN environments. This work contributes to the development of optimization techniques for multimedia transmission over resource-constrained wireless networks, applicable in real-time monitoring systems.